Provenance Variation in Seed and Seedling Attributes of Jamun (Syzygium cumini Skeels) - Soratur, Ramanagouda; Harne, S. S. (Indian Forester, 2017)
The present investigation entitled ''Provenance variation in seed and seedling attributes of jamun (Syzygium cumini Skeels)'' was carried out in the Department of Forestry, Dr. P.D.K.V, Akola. During the year 2013-14 and 2014-15 to select some promising selection of wild jamun. Was investigated significant differences were obtained in morphological and seedling attributes with populations.Altitude of seed source showed significant inverse correlation with seed length, seed weight, and seedling weight. But altitude showed significant positive correlation with percentage germination and root collar diameter of seedlings. Significant positive correlation between seed weight and seedling weight and seedling weight was also observed.